Astrocytic JWA Expression is Essential to Dopaminergic Neuron Survival in the Pathogenesis of Parkinson's Disease - Miao, Shu‐Han (CNS Neurosci Ther, 2014)
AIMS: To investigate the role of astrocytic JWA expression in dopaminergic (DA) neuron degeneration and in the pathogenesis of Parkinson's disease (PD). METHODS: Conditional astrocytic JWA null (JWA (∆2/∆2)/GFAP‐Cre) mice and U251 glioma cells were used to evaluate the effects of JWA gene on DA neuron degeneration. The oxidative stress‐driven molecular events were determined in both in vivo and in vitro models. RESULTS: Conditional astrocytic JWA knockout resulted in significant activation of astrocytes measured by increase in glial fibrillary acidic protein‐positive cells (1.34 × 10(3) ± 74.5 vs. 8.44 × 10(3) ± 1.35 × 10(3), P < 0.01) in mouse substantia nigra, accompanied by loss of DA neurons (1.03 × 10(4) ± 238 vs. 6.17 × 10(3) ± 392, P < 0.001). Deficiency of JWA significantly aggravated reactive oxygen species (ROS) accumulation in substantia nigra compared with the wild‐type mice. Increasing JWA expression in U251 glioma cells inhibited ROS with a concomitant increase in intracellular glutathione. Furthermore, suppression of IKK β‐nuclear factor (NF)‐κB signaling pathway was shown to regulate JWA in a PD model. CONCLUSIONS: The JWA gene exerts neuroprotective roles against DA neuronal degeneration via modulating intracellular redox status and NF‐κB signaling pathway and is a potential treatment target for PD.